Method Matters: Comparing Cancer-Related Adjustment of Siblings to Norms and Well-matched Peers. (22nd December 2020) - Tomatsu, Saori C; Stanley, Caroline; Conroy, Rowena; Alderfer, Melissa A
Abstract: Objective : The purpose of this study was to better understand conflicting findings in the literature regarding the adjustment of siblings of children with cancer by examining, in a single sample, differences in patterns of results as a function of reporter and comparator used (i.e., population norms, demographically matched classmates). Method : Self- and parent-report standardized measures of depression, anxiety, and behavioral problems were collected for 67 siblings and 67 demographically matched classmates. Comparisons were made to norms and controls. Results : Siblings consistently demonstrated poorer psychosocial functioning than their demographically matched peers across all measures but their scores did not differ from norms. A significantly greater percentage of siblings fell outside the normal range than that expected in the general population for parent-reported total and internalizing problems, but not for externalizing problems or the self-report measures. Conclusions : Findings regarding the psychological adjustment of siblings of children with cancer differ according to the research methods used. It is important to use rigorous methods such as demographically matched peer comparisons when investigating the impact of childhood cancer on siblings.